زيد بت ثابت رضي الله عنه وجمع القرآن : دراسة تحليلية نقدية - ابراهيم، محمد حسن (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2001)
This study discussed the collection of the Holly Qur'an during the era of the first Caliph Abu Baker El-Siddiq and the position of the Shiates about that matter. It discussed the reason and implications behind the controversial choice of Zaid Bin Thabit for that task. This issue was discussed through answering four basic questions. 1. Was the choice of Zaid Bin Thabit depending only on his skills and talents, or there were other qualifications? 2. Was the existence of some owners of personal copies of the Qur'an supportive or disincentive to the Caliph Abu Baker in collection of the Qur'an? 3. Was the Shiates attitude toward the collection of the Qur'an based on any strong proofs or it was just for altercation an accusation? 4. What are differences between the three collections of the Holly Qur'an? And what was the reason behind each of them? The study has followed an analytical and critical approach to analyze the views of both Orinetalists and Shiates. It looked into the ideas and assumptions of some writers who discussed the collection of Qur'an. The research stated some views about the collection and the choice of Zaid. The study also discussed the various abstracts of researchers about the collection of the Qur'an and the appointment Zaid Bin Thabit despite the objection of Bin Masud. It concluded that the reasons were neither acceptable by the two Caliphs nor applicable to Zaid. That is because Zaid was very tolerant and present at the final recitation of the Angel Gibreel (PBUH) of the Holly Qur'an. The Shiate negation of the Qur'an collection was mainly based on prejudiced projection in which they merely voiced the view of other theological scholars about Islam. The research has come to conclusion that, the Shiite books were mistaken in relating the Qur'anic collection and appointment of Zaid with falsity and lack of authenticity. It rejected that assumption and considered it as a base for all Muslims to neglect their accusation to be incomplete text. Moreover the methodology which was adopted in collecting the Qur'an was one of the evidences of its correctness and authenticity. The study also identified the mistakes and claims of some Muslim scholars and analyzed their pleas and proofs as their subsequent results.